2004
DOI: 10.1090/s0002-9947-04-03607-4
|View full text |Cite
|
Sign up to set email alerts
|

Parameter-shifted shadowing property for geometric Lorenz attractors

Abstract: Abstract. In this paper, we will show that any geometric Lorenz flow in a definite class satisfies the parameter-shifted shadowing property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It is worth to mention studies of the shadowing property for the Lorenz attractor. Komuro [13] proved that (except very special case) geometric Lorenz flow do not have shadowing property (see also [2]), however geometric Lorenz flow has parameter-shifted shadowing property for a wide range of parameters [11].…”
Section: Introductionmentioning
confidence: 94%
“…It is worth to mention studies of the shadowing property for the Lorenz attractor. Komuro [13] proved that (except very special case) geometric Lorenz flow do not have shadowing property (see also [2]), however geometric Lorenz flow has parameter-shifted shadowing property for a wide range of parameters [11].…”
Section: Introductionmentioning
confidence: 94%
“…is the geometric Lorenz flow if it is generated by a geometric Lorenz vector field X (see e.g. [20,21,26] for more details). Let T X be the closure of the set…”
Section: Now We Briefly Describe the Geometric Lorenz Attractormentioning
confidence: 99%
“…Komuro [9] showed that geometric Lorenz flows do not satisfy the (parameter-fixed) shadowing property excepted in very restricted cases. Even so, in [8] it was shown that the geometric Lorenz attractors have the parameter-shifted shadowing property. However, this notion is very technical.…”
Section: Introductionmentioning
confidence: 99%